2015
DOI: 10.1097/iop.0000000000000350
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Development of Orbitopathy in Graves Thyroidopathy Patients

Abstract: TSI level greater than 400 at time of presentation of Graves thyroidopathy may be a useful predictor of risk for development of orbitopathy. This information will help to identify patients likely to benefit from early referral to an ophthalmologist for possible preemptive therapy to prevent the development of orbitopathy. Prospective cohort studies are needed to definitively establish the metrics for TSI as a predictor of orbitopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Stein et al found no significant differences in the risk of developing TED between Caucasians (TED: 527 vs no TED: 5312), Latinos (TED: 38, no TED: 512), African Americans (TED: 26 vs no TED: 358), Asian Americans(TED: 26 vs no TED: 358) and other races (TED:9 vs no TED: 79) 74 . In Takakura et al study, comparisons made between African Americans (RR: 0.63; P = .81), Asians (RR: 0.48; P = .58) and other ethnicities (RR: 1.08; P = .96) found no significant differences in the risk of developing TED and ethnicity 75 . However, Khong et al found significantly increased odds of 2.08 (CI: 1.56 to 2.76; P < .001) in Caucasians in developing TED (TED:482 vs no TED: 283) when compared with non‐Caucasians (TED: 122 vs no TED: 155) 77 …”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Stein et al found no significant differences in the risk of developing TED between Caucasians (TED: 527 vs no TED: 5312), Latinos (TED: 38, no TED: 512), African Americans (TED: 26 vs no TED: 358), Asian Americans(TED: 26 vs no TED: 358) and other races (TED:9 vs no TED: 79) 74 . In Takakura et al study, comparisons made between African Americans (RR: 0.63; P = .81), Asians (RR: 0.48; P = .58) and other ethnicities (RR: 1.08; P = .96) found no significant differences in the risk of developing TED and ethnicity 75 . However, Khong et al found significantly increased odds of 2.08 (CI: 1.56 to 2.76; P < .001) in Caucasians in developing TED (TED:482 vs no TED: 283) when compared with non‐Caucasians (TED: 122 vs no TED: 155) 77 …”
Section: Resultsmentioning
confidence: 95%
“…In total, 26,803 patients were included in the review and 10,667 were diagnosed with thyroid eye disease (TED). Articles included mainly originated from Europe (n = 28), 22‐49 Asia (n = 20), 50‐69 North America (n = 7), 70‐76 Oceania (n = 1) 77 and South America (n = 1) 78 . Table 1 summarizes the results of the meta‐analysis, and a summary of the included articles can be found in the appendix.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study from Australia reported that Caucasians have an increased risk (2.08, 95% CI, 1.56-2.76) of developing GO compared with non-Caucasian ethnicities (29). Conversely, other studies failed to link ethnic origin (including Caucasians, African Americans, Asian Americans, Asians, Latinos) to an increased for the occurrence of GO (30,31). In summary, the role of ethnic factors, if any, remains, for the time being, unclear.…”
Section: Age Gender and Ethnicitymentioning
confidence: 99%
“…Elevated thyroid stimulating immunoglobulin (TSI) levels greater than 400 at the time of presentation may predict the risk for development of orbitopathy, hence should be included in the investigations. [ 3 ]…”
mentioning
confidence: 99%